Does Auditing Detect and Suppress Earnings Management? Evidence from Türkiye - Ahmet Onay; Serdar Benligiray (Istanbul Business Research)
This study examines the relationship between auditing factors and earnings management practices. Specifically, it investigates the effects of audit opinion and audit firm size on earnings management. The methodology is a combination of qualitative and quantitative analyses. We constructed multivariate regression models to test research hypotheses. The contextual analysis of qualified audit reports provides definite segmentations for cross-sectional analysis. The findings suggest that a qualified audit opinion is a significant predictor of incomeincreasing earnings management practices in Türkiye. Major audit firms suppress these practices in line with the argument that they perceive them as a potential litigation threat to their reputation and assets. Firms potentially managing their earnings are observed to have more debt, less equity, and greater financial distress. This research provides comprehensive information for capital market regulators, investors, and other stakeholders to evaluate audit performance in mitigating earnings management problems. The present study contributes to the literature by providing evidence from Türkiye.